2008
DOI: 10.1097/sla.0b013e31815efda5
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Surgery for Primary Hyperparathyroidism (HPT) in Multiple Endocrine Neoplasia-Type 1 and Zollinger-Ellison Syndrome

Abstract: Background-HPT in MEN1 patients with ZES is caused by parathyroid hyperplasia. Surgery for parathyroid hyperplasia is tricky and difficult. Long-term outcome in ZES/MEN1 /HPT is not well known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
121
5
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(141 citation statements)
references
References 55 publications
4
121
5
11
Order By: Relevance
“…The mild biochemical disease contrasted with the early-onset, progressive, frequent, extensive, and severe bone demineralization in our HPT/MEN1 subset. The relative excess of symptomatic HPT patients in our sample (81%) also has been reported in other HPT/MEN1 cohorts, (13,15,16,(26)(27)(28) contrasting with the modern SPHPT series (20%). (21)(22)(23)(24)(25) In addition, our data suggest that the asymptomatic stage of MEN1-associated HPT seems to be relatively short because up to 60% of patients younger than 30 years of age were already symptomatic (urolithiasis).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The mild biochemical disease contrasted with the early-onset, progressive, frequent, extensive, and severe bone demineralization in our HPT/MEN1 subset. The relative excess of symptomatic HPT patients in our sample (81%) also has been reported in other HPT/MEN1 cohorts, (13,15,16,(26)(27)(28) contrasting with the modern SPHPT series (20%). (21)(22)(23)(24)(25) In addition, our data suggest that the asymptomatic stage of MEN1-associated HPT seems to be relatively short because up to 60% of patients younger than 30 years of age were already symptomatic (urolithiasis).…”
Section: Discussionsupporting
confidence: 50%
“…The high prevalence of urolithiasis-related renal comorbidities in this study confirmed previous data, (27) and the high frequency of urolithiasis found in our gastrinoma/HPT patients is in agreement with others. (13) The progressive impairment of renal function that we observed may be related to the early onset of renal calculi, long-standing uncontrolled HPT, and increasing PTH values with aging. The mechanisms leading to the higher susceptibility to urolithiasis in HPT/MEN1 than in SPHPT remain unclear.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, the ZES in MEN1 has to be treated long-term and effectively with a proton pump inhibitor [64] . Furthermore, the presence of hyperparathyroidism in these patients can make medical control of the gastric hypersecretion more difficult with more frequent and higher PPI doses needed [64,65] . It is therefore recommended that the hyperparathyroidism be treated appropriately (surgical resection of at least 3.5 glands) and the patient followed carefully because it can relapse [64,65] .…”
Section: Men1 Gastrinomamentioning
confidence: 99%
“…Furthermore, the presence of hyperparathyroidism in these patients can make medical control of the gastric hypersecretion more difficult with more frequent and higher PPI doses needed [64,65] . It is therefore recommended that the hyperparathyroidism be treated appropriately (surgical resection of at least 3.5 glands) and the patient followed carefully because it can relapse [64,65] . With this in mind, MEN1/ ZES patients should be treated in specialized clinics; the surgical option should be considered only in specialized centers and only after an interdisciplinary discussion of the individual patient.…”
Section: Men1 Gastrinomamentioning
confidence: 99%